Exhumation and Tectonomagmatic Processes of the Granitoid Rocks from Sulawesi, Indonesia: Constrain from Petrochemistry and Geothermobarometry Study - Maulana, Adi; Imai, Akira; Watanabe, Koichiro; van Leeuwen, Theo; Widodo, Sri; Musri, Musri (Indonesian Journal on Geoscience, 2019)
DOI:10.17014/ijog.6.2.153-174Exhumation and tectonomagmatic processes of the granitoid from Sulawesi were discussed using petrochemistry (e.g. petrographic and major element compositions) and geothermobarometry data (mineral chemistry data). Detailed petrographic observations were conducted to determine the mineral composition, texture, and structure of the granitoid rocks, whereas the whole rock composition were determined using XRF method, and the mineral chemistry was analyzed using Electron Microprobe Analyzer (EPMA). The granitoids are classified as calc-alkaline, metaluminous I-type. Pressures of 0.91 to 1.2 kbar and emplacement depths of 3.2 to 4.3 km at temperatures of 677 - 729°C were estimated for Mamasa Pluton. Whereas Masamba Pluton was emplaced at pressures of 2.3 to 2.8 kbar, temperatures of 756 - 774°C, and emplacement depths of 8.2 to 10 km. Moreover, Lalos-Toli and Sony Plutons were emplaced at temperatures of 731 to 736°C and 601 to 609°C, respectively. The pressures varying from 3.1 to 3.3 kbar and 3.2 to 3.4 kbar, equate to an emplacement depth of 11.3 and 11.6 km, respectively. Gorontalo Pluton emplaced at temperatures of 662 - 668°C with the pressure range from 2.6 to 2.7 kbar, is equivalent to 9.3 km deep. Varied oxidation state (ranging from -14 to 19) is inferred from the mineral assemblages, showing a strong association with highly oxidized I-type series granitic rocks. The exhumation rate estimation shows that Mamasa and Masamba Plutons were exhumed respectively at a rate of 0.37 and 1.6 mm/year, whereas Lalos-Toli and Sony Plutons at 1.4 and 2.7 mm/year, respectively. Gorontalo Pluton located in the Northern Sulawesi Province was exhumed at 0.42 mm/year. The rapid exhumation rate of Sony Pluton is attributed to the active vertical movement of Palu-Koro Fault Zone which has been active since Pliocene. It shows that faulting may play an important role in differential exhumation of intrusive bodies in the orogenic belt.